Effect of Fluoride Releasing Bonding Materials on Shear Bond Strength of Orthodontic Brackets - Duygu Yetkin; Gülşilay Sayar (Galenos Yayinevi, 2020)
Objective:The aim of the present study was to compare the shear bond strength (SBS) of three different fluoride-releasing bonding agents with a conventional adhesive system.Methods:Eighty-four extracted human premolar teeth were separated into four groups and embedded in acrylic molds consisting of 21 teeth in each group. Brackets were bonded with Transbond XT in group 1, Clearfil SE Protect Bond in group 2, LED Proseal in group 3, and Opalseal in group 4. After bracket bonding, the teeth were thermocycled 1000 times. SBS test was performed, and Adhesive Remnant Index (ARI) scores of the groups were assessed.Results:One-way analysis of variance test was used to compare the significant differences between the groups. Chi-square and Fisher's exact tests were used to evaluate ARI scores. The Opalseal group showed the highest bond strength, but there was no statistically significant difference between the groups in SBS values (p=0.067). The results of ARI scores were statistically significant.Conclusions:All bonding materials used in the study showed clinically sufficient bond strengths.